Institutional factors and the postgraduate student experience - Jancey, Jonine; Burns, Sharyn (MCB University Press, 2013)
Purpose – Few studies have evaluated the satisfaction of mature-aged postgraduate students. The purpose of this paper is to determine postgraduate coursework students' service expectations in regard to academic course quality, university services and industry links. Design/methodology/approach – A case study of 51 taught postgraduate students enrolled in the School of Public Health nested postgraduate courses was conducted. Students completed an online self-complete survey (response rate of 58 per cent). Descriptive statistics and unilabiate analysis (chi-square) were used to explore associations between variables. Findings – Postgraduate taught students come from a variety of career backgrounds. They place a great deal of importance on their educational experience, especially in regard to academic factors: reputable degree; skilled engaging teachers; access to online resources; ready contact with academics; and supportive enrolment processes. Practical implications – A greater awareness of student expectations equips universities to provide a more meaningful pedagogical experience and to better address the unique needs of postgraduate students. This is likely to enhance lifelong learning and support retention and progression rates. Originality/value – This research provides a case study of a specific group of postgraduate students and helps understand some of the unique requirements of this postgraduate group, which is largely older, female, domestic students.